Invitation to grief in the family context - Breen, Lauren; Szylit, R.; Gilbert, K.; Macpherson, C.; Murphy, I.; Nadeau, J.; Reis e Silva, D.; Wiegand, D. (Routledge, 2018)
Grief is a family affair, yet it is commonly viewed as an individual phenomenon. As an international, interdisciplinary team, we explore grief within a family context across theoretical, research, practice, and educational domains. Families are complex and working with this complexity is challenging but necessary for a holistic view of grief. We therefore encourage an increased focus on theorizing, researching, practicing, and educating using innovative approaches to address the complexities of grief within the context of families. Learnings from within each domain will affirm and enhance the development of family-level thinking and approaches.